2007
DOI: 10.3168/jds.2006-873
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing the Level of Bacillus cereus Spores in Farm Tank Milk

Abstract: In a year-long survey on 24 Dutch farms, Bacillus cereus spore concentrations were measured in farm tank milk (FTM), feces, bedding material, mixed grass and corn silage, and soil from the pasture. The aim of this study was to determine, in practice, factors affecting the concentration of B. cereus spores in FTM throughout the year. In addition, the results of the survey were used in combination with a previously published modeling study to determine requirements for a strategy to control B. cereus spore conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 15 publications
2
49
0
Order By: Relevance
“…This result is in general agreement with those reported by others, which have shown that the presence of B. cereus and B. cereus spores in farm tank milk was significantly higher in summer months than in the rest of the year (Vissers et al . ). Previous studies have also found that the highest concentrations are generally observed during summer and early autumn (Giffel et al ).…”
Section: Resultsmentioning
confidence: 97%
“…This result is in general agreement with those reported by others, which have shown that the presence of B. cereus and B. cereus spores in farm tank milk was significantly higher in summer months than in the rest of the year (Vissers et al . ). Previous studies have also found that the highest concentrations are generally observed during summer and early autumn (Giffel et al ).…”
Section: Resultsmentioning
confidence: 97%
“…To ensure consumer safety and increase patronage of the Ghanaian traditional dairy products, attempts have been made to characterize the dominant microorganisms and to select starter cultures for the production of quality and safe products [24, 25]. The incidence of Bacillus cereus on dairy farms and in milk products has been reported elsewhere, particularly in Scandinavia, the Netherlands, Australia and Brazil [2629]. However, there is currently no reported study on the prevalence of Bacillus cereus in dairy farms and milk products in Ghana, and their associated virulence and antibiotic resistance profile.…”
Section: Introductionmentioning
confidence: 99%
“…2008). The increased aerobic spore concentration in farm tank milk during the spring and summer months has been associated with the contamination of teats with soil during grazing (Vissers et al. 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Their spores survive pasteurization, germinate, outgrow, and they have been linked to spoilage of raw and pasteurized milk and dairy products such as fermented and ultra heat treated (UHT) milk (McGuiggan et al 2002;Coorevits et al 2008). The increased aerobic spore concentration in farm tank milk during the spring and summer months has been associated with the contamination of teats with soil during grazing (Vissers et al 2007). During the housing period, the teats can be contaminated by faeces, feed and bedding material: hay and dust have been considered important sources of contamination in winter (Magnusson et al 2007;Christiansson et al 1999).…”
Section: Introductionmentioning
confidence: 99%